Receta básica de Cocinando con Elisa: Ingredientes a la Grimm en una caldera argentina - Garavito, Lucía (Latin American Theatre Review, 2005)
Although French cuisine and violence seem to be the main components in Laragione’s Cocinando con Elisa, the fairytale tradition supplies a more subtle and all pervasive ingredient. The power struggle between Nicole (the chef) and Elisa (her apprentice) is structured around a series of intertextual fairytale motifs – the witch/stepmother, the ogre, the poisonous potions, the naive young woman, the impossible tasks, the incantations – which point towards the reappearance of the witch and her evil arts in a familiar social and political context. By incorporating some of the traditional patterns associated with fairytales and dismantling others, Laragione’s play reveals the horrors of the repressive years of the dictatorship in Argentina. (LG)